Palladium–iridium nanocrystals for enhancement of electrocatalytic activity toward oxygen reduction reaction. (January 2016) - Yang, Tao; Ma, Yanxia; Huang, Qingli; Cao, Guojian
Abstract: Exploiting nanomaterials with high electrocatalytic activity toward oxygen reduction reaction (ORR) and desirable durability in acid media has been recently one of the most significant tasks for developing electrochemical devices. Pd based nanostructures have received considerable interest owing to their Pt analogous surface and ever increasing catalytic performance. We herein report a series of Pd–Ir bimetallic nanoparticles with wire or dendritic shapes in a wide composition range, which were synthesized through a facile hydrothermal strategy. Such nanostructures featured with large electrochemical active surface area (EASA), show comparable catalytic activities to that of commercial Pt catalyst. More importantly, the catalysts display much high durability, as an example, Pd1 Ir2 losses 6% in EASA and 12% in mass activity after 10, 000 potential sweeps, in contrast to respective losses of 42% and 58% for commercial Pt/C counterparts. The remarkable durability was also revealed in actual fuel cells supplied with hydrogen and air. The work demonstrates that these Pd–Ir nanostructures with enhanced performance are promising for practical electrocatalytic applications. Graphical abstract: Highlights: Pd–Ir nanoparticles as highly efficient electrocatalysts toward ORR are demonstrated. The Pd–Ir catalysts display much higher durability compared with Pt/C catalyst. The Pd–Ir nanostructures are synthesized through a facile hydrothermal strategy.